EL AFIANZAMIENTO EXIGIDO EN EL ART. 233,1 DEL CÓDIGO TRIBUTARIO, CONTRAVIENE EL PRINCIPIO CONSTITUCIONAL DE GRATUIDAD AL ACCESO DE JUSTICIA - SÁNCHEZ MONTAÑO, ALEXANDER WLADIMIR (2016)
This research work deals ". The consolidation required in Article 233.1 of the Tax Code, violates the Constitutional principle of free access to justice", its development is important because the constitution of the Republic of Ecuador guarantees Free access to justice, however, there are rules of a lower rank as the tax code that forces to follow an administrative procedure, the claimant must pay an amount of 10 percent of the tax determined by the tax authorities, known as consolidation . This imposition by the State to pay a value as court fee is absurd then remember court fees was repealed and any judicial procedure is free, however, as are actions that go against State institutions, create autonomous rules to benefit the revenue resources, or turn to desist actor, just as the State would benefit from the abandonment of the cause. It requires that in any proceedings is to pay amounts which affects the interests of citizens, who are to meet this consolidation required to put aside the proceeding. The theoretical, legal and doctrinal gathering, conducting surveys and interviews yielded widely recognized criteria clear and precise basis of literature, which contributed to the verification of the objectives and the testing of the hypothesis concerning this practice; both the Constitution of the Republic of Ecuador, like other tax laws criminalizing the procedure and procedural principles to be compulsorily implemented by the authorities, such as the right to free access to the justice system and we meet in the tax litigation procedure.